Pengaruh Penerimaan E-learning Besmart terhadap Self-Directed Learning Mahasiswa: Pendekatan Technology Acceptance Model: The Influence of Besmart E-learning Acceptance on Students' Self-Directed Learning: A Technology Acceptance Model Approach - Mufida Husain; Anik Ghufron (ITScience (Information Technology and Science), 2026)
Student acceptance of Learning Management Systems (LMS) is a crucial factor in supporting the effectiveness of online learning in higher education. Besmart is a Moodle-based LMS used at Yogyakarta State University (UNY), enabling students to access materials, complete assignments, and engage in discussions independently. However, research on LMS technology acceptance in Indonesia has largely focused on variables such as intention or system usage behaviour, often failing to address self-directed learning as a more substantive outcome—particularly in the context of Besmart UNY. This study employed a quantitative approach using an explanatory survey method. Data were collected via online questionnaires from 180 active Besmart students, selected through purposive sampling. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software. The results indicate that all construct indicators met the required validity and reliability criteria. Perceived ease of use (B = 0.387; t = 4.965; p < 0.05) and perceived usefulness (B = 0.472; t = 6.354; p < 0.05) both exerted a positive and significant influence on self-directed learning, with these two constructs explaining 67.6% of the variance (R² = 0.676). Acceptance of Besmart—specifically perceived usefulness—contributed significantly to student self-directed learning; consequently, future LMS development should prioritise enhancing substantive benefits that support users' independent learning processes.